Infección y síntomas progresivos ocasionados por Ceratostomella fimbriata en el cacao - Chong Gómez, L. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Ceratostomella fimbriata grew and sporulated well on potato-destrose-agar and on sawdust from cacao wood beneath the cambium. Inoculation with pure cultures into wounds resulted in infection when applied to the cambial zone of cacao trees. Symptoms were perceptible from 7 to 22 days after inoculation on young plants, and from 4 to 7 months on old or mature plants. Differences in response to inoculation were observed in different clones and hybrids. Inoculation at different hours of the day resulted in different degrees of infection.